Utility of preoperative blood screening before hip and knee arthroplasty. Issue 3 (20th January 2020) - Shumborski, Sarah; Gooden, Benjamin; Salmon, Lucy J.; O'Sullivan, Michael; Pinczewski, Leo A.; Roe, Justin P.; Martina, Kaka; Chopra, Sarthak; Maclean, Colin; Lyons, Matthew C.
Abstract: Background: It is engrained in medical training that routine blood screening prior to arthroplasty is necessary for optimal patient care. There is little evidence to support their utility and the aggregate cost to the health system. The purpose of this study was to evaluate preoperative blood screening by identifying the frequency of an abnormal result and to examine the influence of age, gender and body mass index on the frequency of abnormal blood pathology. Methods: This is a retrospective review of 1000 patients from a single centre who underwent elective primary hip or knee arthroplasty from 2015 to 2017. Abnormal blood results were identified and clinically relevant intervals were created for routine markers. Results: A total of 939 patients had available pathology results with 84% identified as having an abnormal result and 47% having a clinically important range. Abnormal liver function tests and ferritin were most common. With increasing age, there was a significant increase in rates of abnormal clinically important range, renal dysfunction, abnormal haemoglobin and erythrocyte sedimentation rate. Males and patients with body mass index >40 had an increased rate of abnormal results, particularly liver function tests. Conclusion: The ordering of preoperative investigations prior to lower limb arthroplasty is recommended by the National Institute for Health and Care Excellence guidelines, alleviating concern of post‐operative complications and covering medicolegal issues. Our study determined a high frequency of abnormal results, justifying routine blood screening is recommended prior to surgery, particularly for the elderly, males and obese patients. Abstract : In a study of preoperative blood screening of 1000 subjects undergoing primary hip (THA) or knee arthroplasty (TKA), our study determined a high frequency of abnormal results, justifying routine blood screening is recommended prior to surgery, particularly for the elderly, males and obese patients.